ENGINEERED GEOPOLYMER CONCRETE USING CHOPPED COCONUT FIBERS - LEONG , YEE HONG (IRC, 2019)
Many efforts and research have been done to discover alternative material to replace Ordinary Portland Cement (OPC) throughout the years. OPC has been well known by the industry due to its high compressive strength and high durability characteristics. However, producing OPC brings along tons of disadvantages that polluted planet Earth. In recent years, fly ash based geopolymer binders have been identified as one of the best alternatives to replace OPC which leads to green construction process. Engineered geopolymer concrete can be classified as a high performance composite due to its process to enhance the properties of geopolymer to achieve high compressive strength and ductility. In this paper, different percentage of coconut fibre added would be used as a reinforce fibre in geopolymer concrete to determine the feasibility of this material based on its performance (compressive strength, flexural strength and workability) by performing lab tests.